2012
DOI: 10.1111/j.1468-0491.2012.01571.x
|View full text |Cite
|
Sign up to set email alerts
|

A Tale of Two Courts: The Judicialization of Electoral Politics in Asia

Abstract: This article examines the judicialization of electoral politics in Asia, an important but understudied trend, as demonstrated in Thailand and Indonesia. Though the constitutional courts in both have similar histories and institutional arrangements, their electoral interventions vary radically. We argue that the diffusion or concentration of power among post‐transition elites determines whether the effect of judicial activism will be to shore up or undermine electoral governance. Where power is diffused, as in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 53 publications
1
17
0
Order By: Relevance
“…80 Mietzner 2013. 81 Mietzner 2010;Dressel and Mietzner 2012. The Constitutional Court's reformist credentials were tarnished by revelations in 2013 that Akil Mochtar, then chair of the court, had taken bribes in relation to a series of regional election disputes.…”
Section: Emerging Policy Spacesmentioning
confidence: 97%
“…80 Mietzner 2013. 81 Mietzner 2010;Dressel and Mietzner 2012. The Constitutional Court's reformist credentials were tarnished by revelations in 2013 that Akil Mochtar, then chair of the court, had taken bribes in relation to a series of regional election disputes.…”
Section: Emerging Policy Spacesmentioning
confidence: 97%
“…Elite dynamics not only critically determine whether courts will be propelled into the political fray but, as the cases indicate, they are also critical in shaping behaviour when courts are confronted with mega-political issues. For instance, in Korea and Indonesia, elite configurations have been diffused, allowing for societal acceptance of the courts as final arbiters; there the courts have seized on the political space to not only engage in areas of governance, but also to actively advance the good governance agenda (Dressel and Mietzner 2012). On the other hand, where elites have managed to align the courts to their purposes, as in Thailand, or shown little division amongst each other, as in Singapore, courts are unlikely to even look for room to intervene; nor are they able to actively shape a good governance agenda that might run against engrained elite interests.…”
Section: B Dresselmentioning
confidence: 99%
“…109 In light of these experiences, a number of commentators have argued that the case of the Indonesian Constitutional Court "has demonstrated that judicial intervention related to elections can in fact promote democratic consolidation." 110 Indeed, in deciding electoral disputes, the Indonesian Constitutional Court had become "activist" in a number of ways. The court began, from November 2008 onwards, to review the quality of the election process itself (such as the nomination of candidates, the abuse of power by incumbent candidates, etc.).…”
Section: B the Indonesian Constitutional Courtmentioning
confidence: 99%
“…With this decision, the Constitutional Court had become a "positive legislator", thereby moving beyond its role as a "negative legislator" as envisaged in the Constitution, and thus formally "overstepping the boundaries of its authority". 112 What is remarkable in the case of the Indonesian Constitutional Court is that although the court moved from being a mere "negative legislator" to being a "positive legislator", and although it went beyond its authority as circumscribed by the Constitution, it has not suffered the negative consequences that other constitutional courts in emerging democracies have faced. 113 Indeed, although the court's "activist" approach has been criticised by legislators, who are of the view that the court has unduly overstepped the boundaries of its authority and entered the area of law-making, the Constitutional Court is, overall, a highly respected and popular institution in Indonesia.…”
Section: B the Indonesian Constitutional Courtmentioning
confidence: 99%
See 1 more Smart Citation